The Effect of Green Finance On Stock Price Volatility - Ernst Tunggul Pardomuan Siregar; Bangkit Nata Satria M (Eduvest - Journal of Universal Studies, 2023)
This study aims to determine the effect of green finance (green accounting) on stock price volatility. Stock price volatility is the movement of up and down stock prices on the stock exchange. In this study, the sample used was mining companies listed on the Indonesia Stock Exchange for the 2013-2018 period with a total population of 46 companies. With purposive sampling technique, get 18 companies as samples. This study used the panel data regression method with a common effect model approach. The results showed that a green finance has a positive effect on stock price volatility. Information asymmetry as a moderation variable cannot amplify the influence of green finance on stock price volatility, and also the effect of quality environmental and social disclosures on stock price volatility